(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents the opinions of our country and foreign scholars on the Lexical-Semantic Features of Modal Verbs in Fairy Tales (on the Example of English and Uzbek Fairy Tales). The topic "Lexico-Semantic Features of Modal Verbs in Fairy Tales (on the Example of English and Uzbek Fairy Tales)" suggests an analytical study of how modal verbs function within the linguistic and cultural contexts of fairy tales in English and Uzbek languages. The topic "Lexico-Semantic Features of Modal Verbs in Fairy Tales (on the Example of English and Uzbek Fairy Tales)" can explore fascinating linguistic phenomena in two rich traditions.